A COMPARATIVE STUDY ON THE EFFECTS OF SPINAL VERSUS GENERAL ANAESTHESIA ON APGAR SCORE OF THE NEONATES AMONG PATIENTS ENDURING ELECTIVE CAESAREAN SECTION - Dr Mukhtiar Ali; Dr Zaman Ali Jokhio; Dr Vijay Kumar; Dr Irfan Ali; Dr Saif Ali Shaikh (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Objectives : The purpose of this research is to establish the use of spinal versus general anesthesia for elective caesarean section and how it affects the Apgar score among neonates together with the maternal and neonatal outcomes.Materials and Methods : A cross-sectional study was planned among 200 women who were planned for elective cesarean sections at multiple centers incuding Department of Anesthesiology, Isra University Hospital Hyderabad, Pakistan and Department of Anaesthesiology and Surgical ICU Liaquat University of Medical and Health Sciences Hospital Jamshoro Hyderabad, Pakistan. Participants were divided into two groups based on the type of anesthesia administered: Local anesthesia that involves the use of spinal anesthesia and general anesthesia. Maternal characteristics, initial apgar scores, and neonates that required resuscitation were recorded and compared.Results : These studies revealed neonates who were delivered under spinal anaesthesia had better mean Apgar scores at 1 minute as compared to those delivered under general anaesthesia. Nevertheless, spinal anaesthesia was found to increase the rate of maternal hypotension and vasopressor use. Neonatal resuscitation rate was however higher in general anaesthesia but maternal haemodynamics were more stable during the procedure.Conclusion :Regarding the neonatal Apgar scores, spinal anesthesia has little advantage compared with epidural anesthesia but has more impact on maternal cardiovascular stability. Each of these two sorts of anesthesia has relative merits and demerits; they cannot be delivered in an impersonal manner.